Barriers to mental health treatment for children and adolescent: a systematic review - Abdul Ghani, Siti Fatimah; Mohd Zulkefli, Nor Afiah; Baharom, Anisah; Minhat, Halimatus Sakdiah (2015)
Background: Despite the higher prevalence of mental health problem among children and adolescent, the rate of mental health services utilization among this group is still low. Among small number of children and adolescents attended mental health treatment, many of them tend to prematurely terminate the treatment offered.